2013
DOI: 10.1103/physrevb.88.241106
|View full text |Cite
|
Sign up to set email alerts
|

Large lattice distortions associated with the magnetic transition in La0.7Sr0.3MnO3

Abstract: Col ossal magnetoresistance (CMR) is associated with the phase transition from a metallic ferromagnetic to insulating paramag netic phase, which can be controlled by an applied magnetic fiel d. The insulating phase occurs due to trapping of the charge carriers by polaronic lattice distortions, which raise the resistivity. Theories based on local physics predict that the magnitude of the resistivity jump at T c is determined by how much, on average, the amplitude of these distorti ons increases at the phase tra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
2
7
0
Order By: Relevance
“…However, experiments on manganite materials have not found evidence of significant coupling at the crossing between the spin wave and phonon branches [20][21][22]. The lattice and magnetic degrees of freedom are however coupled in the polaron regime above T C [23], and in a variety of manganite compounds the local distortions in the crystallographic position of oxygen atoms have been found to increase at T C [24,25] while acoustic phonons in La 0.7 Sr 0.3 MnO 3 soften and broaden when heated through T c [26]. A later work by Ye, et al [12] reported significantly damped excitations, with Γ (the full-width at half-maximum, FWHM) reaching 20 meV along the [110] direction and 60 meV along the [111] direction, but no abrupt change in broadening.…”
Section: Figmentioning
confidence: 99%
“…However, experiments on manganite materials have not found evidence of significant coupling at the crossing between the spin wave and phonon branches [20][21][22]. The lattice and magnetic degrees of freedom are however coupled in the polaron regime above T C [23], and in a variety of manganite compounds the local distortions in the crystallographic position of oxygen atoms have been found to increase at T C [24,25] while acoustic phonons in La 0.7 Sr 0.3 MnO 3 soften and broaden when heated through T c [26]. A later work by Ye, et al [12] reported significantly damped excitations, with Γ (the full-width at half-maximum, FWHM) reaching 20 meV along the [110] direction and 60 meV along the [111] direction, but no abrupt change in broadening.…”
Section: Figmentioning
confidence: 99%
“…The polaronic metal character of La 0.7 Ca 0. become paramagnetic polaronic insulators with static polarons [8,14], whereas LSMO becomes a paramagnetic polaronic metal with mobile polarons. This explains why the absolute strength of magnetoresistance near 𝑇 𝐶 in LSMO and La 1.2 Sr 1.8 Mn 2 O 7 differs by more than an order of magnitude [20]. Phase separation between charge-ordered (CO) and ferromagnetic metallic regions is discussed in CMR manganites since more than 15 years [29] and, recently, CMR in undoped LaMnO 3 under an applied pressure of 𝑝 = 32 − 35 GPa was also explained in this scenario [30].…”
mentioning
confidence: 97%
“…So the point of view emerged that the metallicity, high T C, and small CMR effect in LSMO, are well explained by DE physics without JT polarons [3]. However, in a recent experiment [20] some of us demonstrated that the lattice distortions in LSMO increase at 𝑇 𝐶 similarly to other manganites having a much larger magnetoresistance effect. Small polarons in LSMO were reported by pulsed neutron diffraction as well a [21].…”
mentioning
confidence: 99%
“…Acting as extended defects though, both these interface-effects provide increased scattering of the charge-carriers, adding to the dc resistivity ρ 0T [37]. Consequently, field-dependent topological rearrangement of coexistent phases (FM tubules in PM matrix say, [14]) and of the associated local isostructural variations across their "domain-walls" reflect in the (ac) permittivity directly, and alter the (dc) resistance mainly via their across-the-sample percolative-reorganization; manifesting MR dcindependent (magneto-dielectric) ac effect at high-frequencies.…”
Section: Transition) Does Not Indicate a Ferroelectric (Fe) Transitiomentioning
confidence: 99%